Impact of aortic rather than brachial pulsatile haemodynamics on variations in end-organ measures across the full adult blood pressure range. Issue 12 (December 2017) - Hodson, Bryan; Norton, Gavin R.; Ballim, Imraan; Libhaber, Carlos D.; Sareli, Pinhas; Woodiwiss, Angela J.
Abstract : Aims: To determine the extent to which the adverse effects of blood pressure (BP) are mediated by pulsatile haemodynamic changes across the normotensive as compared with the hypertensive adult brachial BP range, and whether aortic rather than brachial pulsatile changes best index these effects. Methods: In 1307 community participants, the contribution of pulsatile haemodynamics (applanation tonometry and SphygmoCor software) to variations in left ventricular mass index (LVMI) (echocardiography) ( n = 920), carotid intima–media thickness (IMT) ( n = 712) and estimated glomerular filtration rate (eGFR) ( n = 1164) were assessed. Results: In normotensive participants (50.5%) independent of steady-state pressure (mean arterial pressure), significant relations between aortic backward wave pressure and LVMI (partial r = 0.16, P < 0.001) or IMT (partial r = 0.15, P < 0.005) and between aortic pulse wave velocity and eGFR (partial r = −0.18, P < 0.0001) were noted, effects which in hypertensive participants were observed for LVMI and eGFR, but not IMT. With adjustments for brachial pulse pressure (PP) or SBP and confounders, aortic backward wave pressure and aortic pulse wave velocity showed independent relations with LVMI, IMT or eGFR in normotensive participants, but only with LVMI or eGFR in hypertensive participants. In normotensive participants, as compared with brachial PP or SBP, aortic backward wave pressure showed a greater slope (β-coefficient) of the relation with LVMI (0.99 ± 0.24 versus 0.47 ± 0.10 and 0.41 ± 0.09 mmHg, P < 0.05) and IMT (0.0045 ± 0.0013 versus 0.0013 ± 0.0006 and 0.0013 ± 0.0005 mmHg, P < 0.05) and a stronger association with left ventricular hypertrophy [odds ratios (95% confidence interval), 1.125 (1.059–1.195) versus 1.054 (1.027–1.082) and 1.042 (1.020–1.066), P < 0.05]. However, in hypertensive participants, only the slope of the aortic backward wave pressure–LVMI relationship was greater than that of PP–LVMI and SBP–LVMI relations. Conclusion: Beyond brachial BP, pulsatile haemodynamics rather than steady-state pressures account for end-organ effects more consistently across the normotensive than the hypertensive BP range. Hence, targeting aortic pulsatile haemodynamic changes may best limit BP-related cardiovascular risk within the normotensive BP range. Abstract : Supplemental Digital Content is available in the text